Quantitative easing and long-term yields in small open economies - Antonio Díez de los Ríos; Maral Shamloo (Bank of Canada, 2017)
We compare the Federal Reserve's asset purchase programs with those implemented by the Bank of England and the Swedish Riksbank, and the Swiss National Bank's reserve expansion program. We decompose government bond yields into (i) an expectations component, (ii) a global term premium and (iii) a country-specific term premium to analyze two-day changes in 10-year yields around announcement dates. We find that, in contrast to the Federal Reserve's asset purchases, the programs implemented in these smaller economies have not been able to affect the global term premium and, consequently, their effectiveness in lowering long-term yields has been limited.
Keywords: E43; E52; E58; G12; 330; Financial markets; Interest rates; Monetary policy